2010
DOI: 10.4061/2010/263685
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Long-Term Results of Coronary Angioplasty in Patients Aged 80 Years and Older

Abstract: Objectives. To observe the short- and long-term outcomes after percutaneous coronary intervention (PCI) in octogenarians (>80 y.o.) at our institution. Method. All octogenarians who underwent PCI during the study period were retrospectively retrieved from our database and clinically followed. Major adverse cardiac (and cerebral) events (MAC(C)E) was considered as primary outcome. Results. From January 2003 to December 2007, 140 octogenarians (mean age: 85±3 y.o., 79% of male) underwent PCI and were clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Some experimental studies have found that a procoagulant state exists in older patients because of the activation of the intrinsic coagulation system, decreased fibrinolytic activity, or alterations in platelet function. 16,17 Also, it is well-known that older patients with coronary artery disease tend to have more diffused, tortuous, and calcified lesions, which may undoubtedly affect the optimal apposition of the stent to the artery wall, thereby increase the risk of ST. 18 In common with these study’s findings, a large observational cohort study showed that older patients have elevated risk of ST after pPCI. 19…”
Section: Discussionsupporting
confidence: 60%
“…Some experimental studies have found that a procoagulant state exists in older patients because of the activation of the intrinsic coagulation system, decreased fibrinolytic activity, or alterations in platelet function. 16,17 Also, it is well-known that older patients with coronary artery disease tend to have more diffused, tortuous, and calcified lesions, which may undoubtedly affect the optimal apposition of the stent to the artery wall, thereby increase the risk of ST. 18 In common with these study’s findings, a large observational cohort study showed that older patients have elevated risk of ST after pPCI. 19…”
Section: Discussionsupporting
confidence: 60%
“…The reason is thought to be multifactorial. Previous studies have shown that age alone is a strong predictor for short‐ and long‐term mortality after PPCI . Furthermore coexisting geriatric conditions and previous ischemic heart disease with subsequent left ventricular dysfunction may contribute to the unfavourable prognosis .…”
Section: Discussionmentioning
confidence: 99%